T-Cell-Based Immunosuppressive Therapy Inhibits the Development of Natural Antibodies in Infant Baboons (2012)
Background. We set out to determine whether B-cell tolerance to A/B-incompatible alloantigens and pig xenoantigens could be achieved in infant baboons. Methods. Artery patch grafts were implanted in the abdominal aorta in 3-month-old baboons using A/B-incompatible (AB-I) allografts or wild-type pig xenografts (pig). Group 1 (Gp1) (controls, n=6) received no immunosuppressive therapy (IS) and no graft. Gp2 (n=2) received an AB-I or pig graft but no IS. Gp3 received AB-I grafts+IS (Gp3A: n=2) or pig grafts+IS (Gp3B: n=2). IS consisted of ATG, anti-CD154mAb, and mycophenolate mofetil until age 8 to 12 months. Gp4 (n=2) received IS only but no graft. Results. In Gp1, anti-A/B and cytotoxic anti-pig immunoglobulin-M increased steadily during the first year. Gp2 became sensitized to donor-specific AB-I or pig antigens within 2 weeks. Gp3 and Gp4 infants that received anti-CD154mAb made no or minimal anti-A/B and anti-pig antibodies while receiving IS.